Will Obama really rise to the occasion? - Abd Razak, Dzulkifli (2009)
AMERICAN President Barack Obama, at a recent news conference on the MiddleEast, wanted the US to "start by listening!" This was a departure from the previous US administration which Obama admitted would "start by dictating!" There is no better time to start listening than now when the guns are largely silent on all fronts although their impact remains deafening given the horrific consequences. This is the result of a blatantly asymmetric war that is causing pain and suffering to the majority who are defenceless. To be sure, it is a coward's war, an uncivilised way of settling ageold differences. As US commander General David Petraeus once admitted, even the coalition of the willing (in Iraq) "could not kill its way out of the problems of insurgency and civil strife".